Case report: Pediatric anti-gamma aminobutyric acid-B receptor encephalitis with benign prognosis - Wang, Yeping; Ren, Xiaoyan; Shen, Yu; Hua, Yi; Xu, Lu; Zhang, Weiran; Sheng, Guoxia; Jiang, Peifang; Yuan, Zhefeng; Liu, Liu; Gao, Feng (Frontiers in Pediatrics, 2023)
Objective To explore the clinical characteristics of paediatric anti-gamma aminobutyric acid-B receptor (GABABR) encephalitis to enhance the understanding and improve the diagnostic and therapeutic strategies for this disease. Methods This retrospective study reports a case of a female paediatric patient with anti-GABABR encephalitis who was treated at the Children's Hospital of Zhejiang University School of Medicine. Literature search was performed to explore the clinical characteristics of paediatric anti-GABABR encephalitis. Results The patient exhibited recurrent epileptic seizure, status epilepticus, and psychiatric symptoms at the age of 11 years and 10 months. Anti-GABABR antibodies were positive in cerebrospinal fluid and serum. Brain magnetic resonance imaging (MRI) exhibited abnormal signals in the left hippocampus. Symptoms and abnormaility of brain MRI were improved after administration of immunosuppressants, antiseizure and antipsychotic drugs. Two idiopathic cases of paediatric anti-GABABR encephalitis with clinical data were identified through literature search. Analysis of these three cases suggested that the paediatric patients primarily experienced limbic encephalitis, with no tumour incidence. A favourable immunotherapy response was demonstrated with a superior prognosis in all the cases. Conclusions We reported a paediatric anti-GABABR encephalitis case with earliest age of onset. Promt autoimmune antibody testing and tumour screening, as well as immunomodulatory treatment immediately after a definitive diagnosis are warranted to improve prognosis.